Clinical profile of patients with anemia - Lamsal, K. S. (Journal of Institute of Medicine Nepal, 2010)
Introduction: Anemia itself is not a disease but a clinical feature of some other underlying problems and leads to hypoxia and a wide range of clinical consequences. In a tertiary center like Tribhuvan University Teaching Hospital (TUTH), many patients admitted in medical wards have low hemoglobin. The objective of this study is to determine the etiology and evaluate the different components of clinical profile of the patients having anemia in medical wards of TUTH. Methods: Patients having hemoglobin less than 10 in the medical wards of TUTH were enrolled in the study. Estimation of hemoglobin and other investigations were done in hematology lab of TUTH. Data were obtained by history taking, examination findings and investigation reports and analysis was done by statistical software SPSS 11.5v. Results: Among the 237 patients, 138 were male and 99 were female. The commonest age group was 40-49 years. The average hemoglobin was 7.8gm%, the lowest being 2.8gm%. Peripheral blood smear showed hypochromic picture in 140, macrocytic picture in 26 and the morphology was normocytic normochromic in 71 cases. Variceal bleeding leading to anemia was seen in 52, NSAID induced GI bleeding in 22 , peptic ulcer in 18, hookworm infestation in 6, nutritional iron deficiency and anemia of chronic diseases in remaining cases. Among the 26 cases having macrocytic anemia, 11 had megaloblastic changes in bone marrow examination and 6 had vitamin B 12deficiency and 5 had folate deficiency. Among the 71 patients having normocytic normochromic blood picture, 8 had hemolytic anemia, 11 had aplastic anemia and remaining were having anemia of chronic disease mainly chronic kidney disease. Regarding treatment, 84 patients were transfused blood. Out of total 237 patients included in the study, in-hospital mortality was 28. Conclusions: Anemia is associated with a variety of diseases. As chronic blood loss and iron deficiency are among the leading causes of anemia, hypochromic and microcytic picture was the predominant picture in peripheral blood smear. Among the patients having normocytic normochromic blood picture, majority were having chronic kidney disease which may be due to the fact that TUTH is a tertiary referral centre for chronic renal failure. In-hospital mortality due to anemia alone is lower in tertiary care centers, but the mortality in our study is due to associated co-morbid conditions like chronic renal failure and variceal upper GI bleeding. Keywords: Anemia, hemoglobin, iron deficiency. DOI: 10.3126/joim.v31i3.2994 Journal of Institute of Medicine, December, 2009; 31(3) 30-33